Cryptographic Technology and Anti-Money Laundering Policies Against the Sale of Drugs Using Bitcoin Transactions - Hermansyah, Firman; Fajar, Ahmad; Margayasa, I Ketut; Syahril, Syahril; Rosidawati, Imas (Greenation International Journal of Law and Social Sciences, 2024)
This research aims to analyze the influence of cryptographic technology and the effectiveness of Anti-Money Laundering (AML) policies on countering Bitcoin transaction-based drug trafficking in Indonesia. Using a normative legal research method with a desk study approach, this study evaluates the contribution of cryptography to transaction security, challenges in monitoring, and weaknesses in AML policies in Indonesia. The results show that cryptographic technology enhances the security and efficiency of transactions through blockchain, but its anonymity is utilized in illegal activities. In addition, AML policies in Indonesia still face implementation challenges, such as low compliance with Know Your Customer (KYC) principles and minimal supervision of cryptocurrencies. This research recommends strengthening regulations and international cooperation as strategic steps in tackling digital crime.